Medialization of shaft of humerus to provide medial buttress and prevent varus collapse in 3- and 4-part proximal humerus fractures: review of the surgical technique - Srinivas Kasha, MS(Ortho); Ranjith Kumar Yalamanchili, MS(Ortho); G.P.R.K. Rohit, MS(Ortho); Suresh Krishna Lokayah, MS(Ortho); Varun Kulkarni, MBBS (JSES Reviews, Reports, and Techniques)
Hypothesis: Proximal humerus fractures present a treatment challenge due to varied fracture configurations and a lack of consensus on optimal management. Locking plate designs offer promising solutions, yet technical guidelines for successful outcomes remain elusive. Complications are common, with fixation-related failures often attributed to varus collapse. Addressing this, we review a novel intraoperative technique of medialization of the humerus shaft to provide medial buttress support to the humerus head. Methods: This retrospective study included acute 3-part and 4-part proximal humerus fractures treated with open reduction and proximal humerus locking plate fixation from February 2013 to August 2021, which were restored by creating medial buttress by the described technique. Central Column Diaphyseal angle was measured on the 20° external rotation anteroposterior X-ray radiograph, by measuring the intersection angle of the axis of the proximal part of the humerus and the line perpendicular to the anatomical neck. The functional outcome was measured with the Constant score that assesses pain and shoulder function during daily activities, range of motion, and shoulder strength at each follow-up. Results: Seventy-six patients with acute 3- and 4-part proximal humerus fractures were treated using this technique and followed for an average of 16 months. Results showed successful union in 76% of cases within 12 weeks, with no nonunions or implant failures requiring revision surgery at a minimum of 24 months follow-up. Functional outcomes were favorable in 70% of patients. However, avascular necrosis of the humeral head occurred in 12% of cases. Conclusion: Despite limitations, this technique offers a biomechanically sound approach to enhance fixation stability, potentially improving the outcomes in proximal humerus fractures without the need for any additional fibular grafting procedures.